Ateliers 1992. - Bossé, Laurent; Bruant, Jean-Baptiste; Ergino, Nathalie; Nuridsany, Michel; Pagé, Suzanne; Parent, Béatrice; Partouche, Marc; Prodhon, Françoise-Claire; Sans, Jérôme; Scherf, Angéline; Zabunyan, Elvan (Paris : Musée d'Art Moderne de la Ville de Paris, 1992)
Blanc, Jean-Luc ; Bossu, Sylvia ; Bruant, Jean-Baptiste ; Closky, Claude ; Faulon, Laurent ; Ferrer, Anne ; Goria ; Gronon, Philippe ; Haroutiounian, Jean-Marc ; Bris, Marc Le ; Mayaux, Philippe ; Mouillé, Thierry ; Neu, Patrick ; Pesce, Anne ; Ramette, Philippe ; Reip, Hugues ; Serres, Pierre-Jean ; Sigurdsson, Sigurdur Arni ; Sorin, Pierrick ; Carrés, Trois ; Volle, Annick ; Andrevon, Philippe ; Espiau, Bénédicte ; Girardeau-Cuckovic, Laure ; Jean, Lydie dit Pannel ; Magnant, Franck ; Vayssié, César
biografie
Frans
kunstcatalogus